Okak : [19--] - Hoy, Frederik Christian, 1877-1960. (2001)
Photograph of the church, mission buildings, Inuit houses, and small boats in the harbour at Okak. Photograph of the church, mission buildings, Inuit houses, and small boats in the harbour at Okak.